Analysis of Outdoor Activity Space-Use Preferences in Rural Communities: An Example from Puxiu and Yuanyi Village in Shanghai - Ledi Wen; Lei Sima (Land, 2022)
The creation of outdoor activity spaces in rural communities is an important indicator to enhance the happiness of villagers and an important means to promote rural revitalization through improving the living environment. However, the urbanization trend of spatial forms has caused problems in the construction of many new rural activity spaces, such as the homogenized design and the lack of attention to the real demands of local residents. In order to understand urban-rural differences as well as inter-rural difference of outdoor activity space preferences in today’s China, so as to optimize the planning and design of public space optimization in rural communities, this study took Puxiu and Yuanyi Village in the suburbs of Shanghai as examples, executed field questionnaire surveys to ascertain villagers’ general preferences for outdoor spaces as well as their personal diversities. The results suggested that urban-rural differences were generally reflected in the practicability, economy, rurality, and diversity of the spaces, and it was found that there are significant relationships between residents’ preferences and their personal attributes, such as gender, age, and occupation. Moreover, the essentials for optimizing community activity space design that reflect urban-rural differences as well as the characteristics of different types of villages were also discussed.